The Modified Dunn Osteotomy for SCFE: Clinical and Radiographical Results at 3 Years Follow-Up - Guindani, Nicola; Eberhardt, Oliver; Wirth, Thomas; Surace, Michele F.; Fernandez, Francisco F. (The Journal of Hip Surgery, 2017)
The modified Dunn osteotomy (MDO) gained popularity for the treatment of moderate-to-severe SCFE over the past years, even though both indications and outcomes are currently debated. The aim of this study is to evaluate results and complications of MDO consecutively performed at a single institution for severe slipped capital femoral epiphysis (SCFE) (slip angle ≥ 60°). In this retrospective clinical study, 23 hips (22 patients) were treated with MDO (2009–2015). SCFE was classified according to stability, slip angle, and as chronic/acute. Clinical assessment was performed with clinical examination and nonarthritic hip score (NAHS), modified Harris hip score (mHHS), and short form 12 (SF-12) outcome scores. Residual deformity, avascular necrosis (AVN), and osteoarthrosis (OA) were measured on plain radiographs. The mean slip angle was 70° (range 60–90); 17 of 23(74%) patients had a chronic SCFE, 6 of 23(26%) had acute-on-chronic SCFE, and 1 of 23(4%) had an unstable SCFE. The mean age at surgery was 14 years (range 11–17). At 3 years follow-up (range 1–7), 4 of 23(17%) patients had an AVN or AVN progression, one of these needing a hip arthroplasty. All the cases of AVN or AVN progression were diagnosed within the first year after surgery and there was an association between AVN and operation date (with more AVN among patients operated earlier). Out of 23 patients, 2 (9%) had an implant mobilization or failure and needed a revision surgery without further complications, 1 (4%) developed an asymptomatic heterotopic calcification, and another a partial implant removal without clinical consequence. At follow-up, the slip angle was 9° (range 1–15) and outcome scores were improved. MDO is a demanding technique which allows a near anatomical correction of SCFE and the overall complication rate is not negligible. With actual data, the authors only recommend this procedure for specialized centers, performed by experienced high-volume surgeons, and for severe displaced SCFE (≥50°). The long-term results must be closely monitored and compared with the natural history and other treatment options. This study was a Level IV retrospective study in a case series.
Keywords: modified Dunn osteotomy; slipped capital femoral epiphysis; subcapital osteotomy; subcapital realignment